The Drm-Bowl-Lin relief-of-repression hierarchy controls fore- and hindgut patterning and morphogenesis. - Johansen, K.A.; Green, R.B.; Iwaki, D.D.; Hernandez, J.B.; Lengyel, J.A. (Mechanisms of Development, 2003)
The elucidation of pathways linking patterning to morphogenesis is a problem of great interest. We show here that, in addition to their roles in patterning and morphogenesis of the hindgut, the Drosophila genes drumstick (drm) and bowl are required in the foregut for spatially localized gene expression and the morphogenetic processes that form the proventriculus. drm and bowl belong to a family of genes encoding C(2)H(2) zinc finger proteins; the other two members of this family are odd-skipped (odd) and sob. In both the fore- and hindgut, drm acts upstream of lines (lin), which encodes a putative transcriptional regulator, and relieves its repressive function. In spite of its phenotypic similarities with drm, bowl was found in both foregut and hindgut to act downstream, rather than upstream, of lin. These results support a hierarchy in which Drm relieves the repressive effect of Lin on Bowl, and Bowl then acts to promote spatially localized expression of genes (particularly the JAK/STAT pathway ligand encoded by upd) that control fore- and hindgut morphogenesis. Since the odd-family and lin are conserved in mosquito, mouse, and humans, we propose that the odd-family genes and lin may also interact to control patterning and morphogenesis in other insects and in vertebrates.